Whose Foreign Policy? Britain's 'Inner Cabinet' and the Eastern Crisis, January–March 1878. Issue 3 (2nd July 2016) - Hicks, Geoffrey
ABSTRACT: This article considers one aspect of Britain's "great Eastern crisis" of 1875–1878. It examines in detail the claims that for two months in early 1878, an "inner Cabinet" led by the prime minister, Benjamin Disraeli—Lord Beaconsfield—in effect replaced the foreign secretary, Lord Derby. With the full range of evidence relating to the "inner Cabinet" never previously explored, this analysis assesses the critical diplomatic phase and the way in which that phase was represented in the context of the 1879–1880 general election campaign. It suggests that electoral considerations drove senior Conservative politicians to construct a retrospective narrative of foreign policy, which has in turn affected the historiography. Exploring the story of the "inner Cabinet" addresses unanswered questions about 1878, accounts for the story's later emergence, and at the same time illuminates party-political debate about foreign policy.